2013
DOI: 10.1108/jcm-02-2013-0482
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of human values in planned behavior: the case of Chinese consumers' intention to buy organic food

Abstract: The moderating role of human values in planned behavior: the case of Chinese consumers' intention to buy organic food

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(173 citation statements)
references
References 52 publications
11
147
0
4
Order By: Relevance
“…For example, studies have found that consumers' value priorities moderate the relationship between consumer attitudes and intentions regarding buying organic food (Zhou et al, 2013). Favourable attitudes are more likely to be transformed into buying intentions the more compatible buying organic food is with the consumer's basic value priorities.…”
Section: Attitudes and Behaviour Towards Organic Foodmentioning
confidence: 99%
“…For example, studies have found that consumers' value priorities moderate the relationship between consumer attitudes and intentions regarding buying organic food (Zhou et al, 2013). Favourable attitudes are more likely to be transformed into buying intentions the more compatible buying organic food is with the consumer's basic value priorities.…”
Section: Attitudes and Behaviour Towards Organic Foodmentioning
confidence: 99%
“…A given behavior possibly occurs when an individual has both the ability and motivation to perform that behavior rather than when the individual has only one or neither factors [75]. According to the TPB model, developing perceived behavioral control prior to generating intention is essential.…”
Section: Perceived Behavioral Control (Pbc)mentioning
confidence: 99%
“…Therefore, such products that use material safer to the environment are recyclable and require less packaging (Chen & Chai, 2010;Ottman, 2011) which are taken into consideration of ecological goodness and society at par. In the study of green consumer psychology, researchers approached "attitude-intention" model underpinned by Fishbein and Ajzen's (1975) the theory of reasoned action (TRA) and Ajzen and Fishbein's (1980) TPB to be predicted purchase behaviour for various categories of eco-friendly products, for instance; energy saving products (Ha & Janda, 2012), green packaging (Prakash & Pathak, 2017), skin care products (Hsu, Chang, & Yansritakul, 2017), organic food (Zagata, 2012;Zhou, Thøgersen, Ruan, & Huang, 2013), and sustainable textile products (Kang, Liu, & Kim, 2013). Despite the popularity of TRA and TPB, several scholars were observed no direct influence of attitude on buying behaviour for green products driven by the components of attitude, subjective norms, and perceived behavioural control (Joshi & Rahman, 2015;Tan, 2011).…”
Section: Green Buying Behaviourmentioning
confidence: 99%